A mobile ad-hoc network (MANET) implementation on android - Mohammed, Mohammed Khalid Hassan (2014)
The continual changing of self-organizing nodes located in an infrastructure-less mesh network is called ad hoc network. The recent years have witnessed a rapid growth of interest in ad hoc networking. This research with the aid of Java Native Interface (JNI) and UNIX kernel tools for network, a method to build a Mobile Ad hoc Network (MANET) has been implemented for Android devices to provide supplementary way of communication in certain situations where network infrastructure does not exist or available. The layered approach that has been adopted was based on abstracting and classifying communication functionality and furthermore facilitates the implementation phase. The first layer tackled the kernel level and modified the wireless tools responsible for manipulating the network interface of the device. The second layer contained the ad hoc routing protocol logic. The third layer implemented the application that runs over the Ad hoc On Demand Distance Vector (AODV) protocol. Based on the data collected from the evaluation phase, MANET solution was able to form an ad hoc network consists of three Samsung mobile devices. The system most of the time reacted in the correct behaviour from a number of testing scenarios conducted on the small test bed. According to the results from the implemented messaging service, it was possible to communicate with any node on the network. The ability to provide data protection to the messages was also provided by implementing an Advanced Encryption System (AES) algorithm using a 256-bit symmetric key. Finally the employed methodology in this research played as an enabler to provide additional services like voice and content sharing without modifying the lower layers.